2021
DOI: 10.1111/jocs.15996
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of pericardiectomy for constrictive pericarditis following mediastinal irradiation

Abstract: Background: Pericardiectomy for postradiation constrictive pericarditis has been reported to generally have unfavorable outcomes. This study sought to evaluate surgical outcomes in a large cohort of patients undergoing pericardiectomy for radiation-associated pericardial constriction.Methods: A retrospective analysis of all patients (≥18 years) who underwent pericardiectomy for a diagnosis of constrictive pericarditis with a prior history of mediastinal irradiation from June 2002 to June 2019 was conducted. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…1,4 Pericardiectomy performed for radiation-associated constrictive pericarditis presented an even higher operative mortality of 10.1%. 5 In our series of patients, we show that isolated pericardiectomy associated with or without tricuspid valve repair can be performed safely with low morbidity and no in-hospital mortality. The use of CPB during totally endoscopic treatment was mandatory to reduce the volume and pressure in the cardiac chambers to detach the pericardium, and in this preliminary series, it did not affect the early outcome.…”
Section: Discussionmentioning
confidence: 54%
“…1,4 Pericardiectomy performed for radiation-associated constrictive pericarditis presented an even higher operative mortality of 10.1%. 5 In our series of patients, we show that isolated pericardiectomy associated with or without tricuspid valve repair can be performed safely with low morbidity and no in-hospital mortality. The use of CPB during totally endoscopic treatment was mandatory to reduce the volume and pressure in the cardiac chambers to detach the pericardium, and in this preliminary series, it did not affect the early outcome.…”
Section: Discussionmentioning
confidence: 54%
“…However, assessing the characteristic hemodynamic features of constrictive pericarditis via general echocardiography may prove difficult and often cause delays in the diagnosis (7), as observed in the present case. In surgical cases, the prognosis of constrictive pericarditis due to radiotherapy is poor, with operative mortality and 10-year survival rates of 10% and 32%, respectively (8). Although the current case was diagnosed at an early stage, surgery for constrictive pericarditis would have been difficult because of the presence of pyothorax.…”
Section: Discussionmentioning
confidence: 81%
“…In fact, mediastinal irradiation is considered an independent prognostic factor for mortality following surgical correction of constrictive pericarditis, with 5-year survival at a dismal 11.0% and an increased 10-year mortality rate [13]. One retrospective study reported an overall intraoperative mortality of 10.1% for patients with a history of mediastinal irradiation over a seventeen-year period, though it should be noted that the majority of those patients underwent concomitant procedures that may have attributed to their outcome [31]. While there have been numerous reports indicating poor outcomes for patients undergoing pericardiectomy following mediastinal radiation treatment, it cannot be overlooked that the increased mortality rates among these patients may be related to their original need for radiation therapy, rather than an interaction between pericardiectomy and irradiated tissue.…”
Section: Etiology Of Constrictive Pericarditismentioning
confidence: 99%